EVALUATION BIOMARKERS ON OPTICAL COHERENCE TOMOGRAPHY IN PATIENTS WITH MACULAR EDEMA DUE TO CENTRAL RETINAL VEIN OCCLUSION WITH ANTIANGIOGENE TREATMENT - Sekerinov, Dejan; Shekerinov, Natasha; Dimovska, Vesna Jordanova; Petrushevska, Andrijana (Journal of Morphological Sciences, 2025)
Retinal vein occlusions (RVO) are the second leading cause of vision loss from retinal vascular diseases in the adult population. Vascular endothelial growth factor (VEGF) plays a major role in the pathophysiology of RVO. The aim of the study is to evaluate structural biomarkers and their impact on acuity, as well as to determine the correlation between visual acuity and the number of applications. The study includes 24 patients with macular edema as a result of central retinal vein occlusion, who are treated with an antiangiogenic drug - Aflibercept. Analysis of SD-OCT/OCTA tomograms was performed at 3 time points (before treatment, at 3 and 6 months) from the start of treatment. Biomarkers were analyzed: Central subfield thickness (CST), presence of epiretinal membrane, change in vascular density in the foveal zone before treatment and at the 6th month of treatment, evaluation of the effect on visual acuity and correlation with intravitreal applications. In the 24 patients (24 eyes) included, a decrease in CST was observed in all. In relation to visual acuity, there was an increase of 2 Snellen lines. Change in the vitreomacular interface was present in 42% of patients. Vascular density was evaluated with OCTA, the change of which was on average from 36.73% ± 11.13 to 23.58% ± 7.26. Antiangiogenic treatment is the first line of treatment for retinal vein occlusions. Timely use of these agents is crucial for better visual acuity, and analysis of biomarkers on optical coherence tomography has prognostic significance. Keywords: vein occlusion, optical coherence tomography, angiography, anti VEGF, biomarkers.